Nonnutritive sweeteners: Pros and cons - Avinash Agarwal; Manish Gutch; Sukriti Kumar; Syed Razi Mohd; Gupta Abhinav Kumar; Keshav Gupta Kumar (Wolters Kluwer Medknow Publications, 2016)
Nonnutritive sweeteners (NNSs) are the substances having an intense sweet taste with no or very low calories and are used as substitutes for simple sugars for reduction of energy intake. The consumption of NNSs is increasing at an alarming rate because of the ever evolving pandemic of obesity and Type 2 diabetes mellitus. NNSs have various positive and negative metabolic consequences on the health of the consumers. There are misconceptions and myths regarding the use of NNSs for which various professional bodies have issued guidelines. However, the overall long-term effects of the NNSs are still an area of debate and discussion.